IN CHOLEDOCHOLITIASIS CHOLEDOXOSCOPY SPECIFIC FEATURES AND PROBLEMS (World Bulletin of Public Health, 2023)
Choledocholithiasis perceived as a disease and its complications as a result of the use of diagnostic and therapeutic purposes in patients with from choledochoscopy improves the results of surgical treatment of patients in this category.
Keywords: Cholelithiasis; choledoxolithiasis; terminal part; the date the papilla